The Armenian holocaust - Hovannisian, Richard, 1932- (My University, 1980)
Beneath the shadow of the First World War, the Young Turk government orchestrated the massacre of over one million Armenians in the Turkish Empire between the years 1915 and 1918. Virtually erased from public memory and forgotten out of political convenience, this attempt to destroy the Armenian population is a prototypical example of genocide which has been repeated throughout the twentieth century. The Armenian Genocide explains the historical, cultural and political conditions which led to this tragedy and to the subsequent claims that it never actually took place. Through exploration of the history, politics and ethics of the Armenian Genocide, this book sheds light on one of the most profound and neglected events in twentieth-century history
a bibliography relating to the deportations, massacres, and dispersion of the Armenian people, 1915-1923
R. G. Hovannisian. - Cambridge : Armenian Heritage Press, National Association for Armenian Studies and Research, 1980. - xvii, 43 p. ; 26 cm.
Contents: Part one: Source materials in selected archives.- Part two: Published documents, accounts, and studies.- Addendum: Recent published accounts and studies
Տվյալները՝ ինտերնետային կայքից
https://archives.webaram.com/dvdk_new/eng/the-armenian-holocaust-hovannisian-1980_OCR.pdf
Keywords: Armenian Genocide, 1915-1923-Bibliography; Armenians-Turkey-Bibliography; Genocide-Turkey-Bibliography